The regulatory roles of the E3 ubiquitin ligase NEDD4 family in DNA damage response - Lu, Xinxin; Xu, Haiqi; Xu, Jiaqi; Lu, Saien; You, Shilong; Huang, Xinyue; Zhang, Naijin; Zhang, Lijun (Frontiers in Physiology, 2022)
E3 ubiquitin ligases, an important part of ubiquitin proteasome system, catalyze the covalent binding of ubiquitin to target substrates, which plays a role in protein ubiquitination and regulates different biological process. DNA damage response (DDR) is induced in response to DNA damage to maintain genome integrity and stability, and this process has crucial significance to a series of cell activities such as differentiation, apoptosis, cell cycle. The NEDD4 family, belonging to HECT E3 ubiquitin ligases, is reported as regulators that participate in the DDR process by recognizing different substrates. In this review, we summarize recent researches on NEDD4 family members in the DDR and discuss the roles of NEDD4 family members in the cascade reactions induced by DNA damage. This review may contribute to the further study of pathophysiology for certain diseases and pharmacology for targeted drugs.